Seismic performance of a floating roof in an unanchored broad storage tank: Experimental tests and numerical simulations. (August 2021) - Caprinozzi, Stefano; Paolacci, Fabrizio; Bursi, Oreste S.; Dolšek, Matjaž
Abstract: Liquid steel storage tanks equipped with floating roofs are critical components of industrial facilities because they often store hazardous material. Major earthquakes have caused large vertical displacements of floating roofs. Consequently, roof failure and/or content loss has occurred, which has seriously endangered the surrounding environment and community. Therefore, research interest in this topic remains high, giving rise to experimental campaigns and investigatory studies concerning design and assessment approaches. The present paper aims to validate a simplified model (SM) using both a refined finite element (FE) model and experimental data. This model could later be used in the vulnerability and risk assessment framework based on numerous seismic analyses. The first part of the paper briefly introduces a shaking table test performed on a scaled steel storage tank equipped with a floating roof. This test provided useful experimental data about the vertical displacement histories of floating roofs subject to seismic loading. Subsequently, both a SM and a refined FE model aimed at simulating the shaking table test are introduced and described. Relevant experimental and numerical outcomes are then presented and discussed. Finally, in order to highlight the most relevant parameters involved, we performed a parametric study related to the SM. It is shown that both the refined FE model and the SM were capable of simulating the roof vertical displacement histories observed in the shaking table test. The former model has higher fidelity but appears to be excessively time-consuming, whilst the latter is more suitable for risk assessment purposes. Highlights: The seismic response of the Floating Roof (FR) in unanchored storage tanks is analysed. Results of an experimental test were used to calibrate a 3D FE model of the entire tank. A simplified non-linear model of the FR was proposed, calibrated and validated. Both FE and simplified models were able to successfully simulate vertical displacements of the roof. The limited computational effort renders the simplified model feasible for risk analysis of tanks with FR.